Representing social action in Indonesian: A case of Indonesian presidential race - Sofyan, Agus Nero; Zifana, Mahardhika (Universitas Pendidikan Indonesia, 2019)
A large body of research on social action representation revolves around how social actors are discursively represented in a variety of media; nevertheless, very few discourse studies have investigated the Indonesian news media portrayal of an Indonesian politician in a number of social events. This research sought to fill in this gap by examining the representation of a prominent Indonesian political figure, i.e. Prabowo Subianto from the lens of two mainstream online Indonesia news media, i.e. Kompas and Republika. More specifically, the prime focus is on outlining types of social action and their grammatical and rhetorical realization in Indonesian discourse. Leeuwen’s (2005; 2008) social semiotics was adopted as the framework of analysis. Ten online news reports—five from each media—focusing on Prabowo were purposively selected on the basis of five key political incidents where Prabowo was engaged. Comparison of two media in their reporting of the events is of special interest, for the representation of the same individual in his socio-political actions can be more apparent and hence media tendencies can be easily identified. Findings reveal that both media have non-neutral, partial tendencies. Their language products entail sympathy and defense of Prabowo, albeit the journalistic code of ethics. More specifically, Republika tends to side with Prabowo’s campaign; while Kompas tends to oppose it. In the form of values, orientation, and tendencies, both media have an ideological tendency to defend or to offend the subject, Prabowo, as is clearly reflected through the distinctive discursive strategies they choose. Implicationally, these results corroborate the long-standing premise that media’s values or ideological stances to a certain extent appear to be a factor in portraying an individual and his/her action in the society, which in turn may influence public perceptions.